Skip to content
Related Articles

Related Articles

Improve Article
Save Article
Like Article

Class 10 RD Sharma Solutions – Chapter 5 Trigonometric Ratios – Exercise 5.3 | Set 1

  • Last Updated : 03 Mar, 2021

Question 1. Evaluate the following:

(i) sin 20°/cos 70°

Solution:

Given: sin 20°/cos 70°

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12. 

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

= sin(90° − 70°)/cos 70°



= cos 70°/cos 70°          -(∵ sin (90° – θ) = cos θ)

= 1

Hence, sin 20°/cos 70° = 1

(ii) cos 19°/sin 71°

Solution:

Given: cos 19°/sin 71°

= cos(90° − 71°)/sin 71°

= sin 71°/sin 71°             -(∵ cos (90° – θ) = sin θ)

= 1

Hence, cos 19°/sin 71° = 1                

(iii) sin 21°/cos 69°

Solution:

Given: sin 21°/cos 69°

= sin(90° − 69°)/cos 69°

= cos 69°/cos 69°            -(∵ sin (90° – θ) = cos θ)

= 1  

Hence, sin 21°/cos 69° = 1                                      

(iv) tan 10°/cot 80°

Solution:

Given: tan 10°/cot 80°

= tan(90° − 80°)/cot 80°



= cot 80°/cot 80°            -(∵ tan (90° – θ) = cot θ)

= 1                                

Hence, tan 10°/cot 80° = 1                      

(v) sec 11°/cosec 79°

Solution:

Given: sec 11°/cosec 79°

= sec(90° − 79°)/cosec 79°

= cosec 79°/cosec 79°          -(∵ sec (90° – θ) = cosec θ)

= 1 

Hence, sec 11°/cosec 79° = 1                

Question 2. Evaluate the following:

 (i) (\frac{sin 49°}{cos 41°})2 + (\frac{cos 41°}{sin 49°})2     

Solution:



Given: (\frac{sin 49°}{cos 41°})2 + (\frac{cos 41°}{sin 49°})

(\frac{sin (90°-41°)}{cos 41°})^2+(\frac{cos 41°}{sin (90°-41°)})^2          -(∵ sin (90° – θ) = cos θ)

= (cos 41°/cos 41°)2 + (cos 41°/cos 41°)2   

= 1 + 1 = 2

Hence, (\frac{sin 49°}{cos 41°})2 + (\frac{cos 41°}{sin 49°})2 = 2     

(ii) cos 48° – sin 42°

Solution:

Given: cos 48° – sin 42°

= cos 48° – sin (90°- 48°)           -(∵ sin (90° – θ) = cos θ)

= cos 48° – cos 48°  

= 0



Hence, cos 48° – sin 42° = 0

(iii)  \frac{cot 40°}{tan 50°}-\frac{1}{2}\frac{cos 35°}{sin 55°}      

Solution:

Given:  \frac{cot 40°}{tan 50°}-\frac{1}{2}\frac{cos 35°}{sin 55°}

\frac{cot(90°-50°)}{tan 50°}-\frac{1}{2}(\frac{cos 35°}{sin (90°-35°)})        -(∵ sin (90° – θ) = cos θ and cot (90° – θ) = tan θ)

\frac{tan 50°}{tan 50°}-\frac{1}{2}(\frac{cos 35°}{cos 35°})

= 1 – 1/2 = 1/2

Hence, \frac{cot 40°}{tan 50°}-\frac{1}{2}\frac{cos 35°}{sin 55°} = 1/2

(iv) (\frac{sin 27°}{cos 63°})2– (\frac{cos 63°}{sin 27°})2      

Solution:

Given: (\frac{sin 27°}{cos 63°})2– (\frac{cos 63°}{sin 27°})2  

(\frac{sin (90°-63°)}{cos 63°})^2-(\frac{cos 63°}{sin (90°-63°)})^2             -(∵ sin (90° – θ) = cos θ)



= (cos 63°/cos 63°)2 – (cos 63°/cos 63°)2    

= 1 – 1 = 0

Hence, (\frac{sin 27°}{cos 63°})2– (\frac{cos 63°}{sin 27°})2 = 0

(v) \frac{tan 35°}{cot 55°}+\frac{cot 78°}{tan 12°}-1

Solution:

Given: \frac{tan 35°}{cot 55°}+\frac{cot 78°}{tan 12°}-1

\frac{tan (90°-55°)}{cot 55°}+\frac{cot 78°}{tan (90°-78°)}-1          -(∵tan (90° – θ) = cot θ)

=(cot 55°/cot 55°) + (cot 78°/cot 78°) – 1

= 1 + 1 – 1 = 1

Hence, \frac{tan 35°}{cot 55°}+\frac{cot 78°}{tan 12°}-1 = 1

(vi) \frac{sec 70°}{cosec 20°}+\frac{sin 59°}{cos 31°}

Solution:



Given: \frac{sec 70°}{cosec 20°}+\frac{sin 59°}{cos 31°}

\frac{sec(90°−20°)}{cosec 20°}+\frac{sin(90°−31°)}{cos 31°}          -(∵ sec (90° – θ) = cosec θ and sin (90° – θ) = cos θ) 

= cosec 20°/cosec 20° + cos 31°/cos 31°

= 1 + 1 = 2

Hence, \frac{sec 70°}{cosec 20°}+\frac{sin 59°}{cos 31°} = 2   

 (vii) cosec 31° – sec 59°

Solution:

Given: cosec 31° – sec 59°

= cosec 31° – sec (90°- 31°)          -(∵ sec (90° – θ) = cosec θ)

= cosec 31° – cosec 31°  

= 0

Hence, cosec 31° – sec 59° = 0

(viii) (sin 72° + cos 18°)(sin 72° – cos 18°)

Solution:

Given: (sin 72° + cos 18°)(sin 72° – cos 18°)

= (sin 72° + cos (90° – 72°))(sin 72° – cos (90° – 72°))          -(∵ sin (90° – θ) = cos θ) 

= (sin 72° + sin 72°)(sin 72° – sin 72°)  

= 0

Hence, (sin 72° + cos 18°)(sin 72° – cos 18°) = 0

(ix) sin 35°sin 55° – cos 35°cos 55°

Solution:

Given: sin 35°sin 55° – cos 35°cos 55°

= (sin 35°sin (90°- 35°)) – (cos 35° cos (90° – 35°))          -(∵ sin (90° – θ) = cos θ and cos (90° – θ) = sin θ) 



= (sin 35°cos 35°) – (cos 35° sin 35°)

= 0

Hence, sin 35°sin 55° – cos 35°cos 55° = 0

(x) tan 48°tan 23°tan 42°tan 67°

Solution:

Given: tan 48°tan 23°tan 42°tan 67°

= tan 48° tan 23° tan (90° – 48°) tan (90° – 23°)           -(∵ tan (90° – θ) = cot θ)

= tan 48° tan 23° cot 48° cot 23°

= 1

Hence, tan 48°tan 23°tan 42°tan 67° = 1

(xi) sec 50°sin 40° + cos 40°cosec 50°

Solution:

Given: sec 50°sin 40° + cos 40°cosec 50°

= (sec 50°sin (90° – 50°)) + (cos 40° cosec(90° – 40°))          -(∵ sin (90° – θ) = cos θ and cosec (90° – θ) = sec θ)  

= (sec 50°cos 50°) + (cos 40° sec 40°)

= 1 + 1 = 2

Hence, sec 50°sin 40° + cos 40°cosec 50° = 2

Question 3. Express each one of the following in terms of trigonometric ratios of angles lying between 0° and 45°

(i) sin 59° + cos 56°

Solution:

Given: sin 59° + cos 56°

= sin (90° – 31°) + cos(90° – 34°)

= cos 31° + sin 34°

(ii) tan 65° + cot 49°

Solution:

Given: tan 65° + cot 49°

= tan (90° – 25°) + cot (90° – 31°)

= cot 25° + tan 31°

(iii) sec 76° + cosec 52°

Solution:

Given: sec 76° + cosec 52°

= sec (90° – 14°) + cosec (90° – 38°)

= cosec 14° + sec 38°

(iv) cos 78° + sec 78°

Solution:

Given: cos 78° + sec 78°

= cos (90° – 12°) + sec (90° – 12°)

= sin 12° + cosec 12°

(v) cosec 54° + sin 72°

Solution:

Given: cosec 54° + sin 72°

= cosec (90° – 36°) + sin (90° – 18°)

= sec 36° + cos 18°

(vi) cot 85° + cos 75°

Solution:

Given: cot 85° + cos 75°

= cot (90° – 5°) + cos (90° – 15°)

= tan 5° + sin 15°

(vii) sin 67° + cos 75° 

Solution:

Given:sin 67° + cos 75° 

= sin (90° – 23°) + cos (90° – 15°)

= cos 23° + sin 15°

Question 4. Express cos 75° + cot 75° in terms of angles lying between 0° and 30°.

Solution:

Given: cos 75° + cot 75°

= cos (90° – 15°) + cot (90° – 15°)

= sin 15° + tan 15°

Question 5.  If sin 3A = cos(A – 26°), where 3A is an acute angle, find the value of A.  

Solution:

Given: sin 3A = cos(A – 26°)

= cos (90° – 3A) = cos(A – 26°)



Now, 90° – 3A = A – 26°

= A + 3A = 90° + 26°

= 4A = 116°

= A = 29°

Hence, the value of A is 29°

Question 6. If A, B, C are the interior angles of a triangle ABC, prove that

(i) tan (C + A)/2 = cot B/2

Solution: 

According to the question

In triangle ABC, A, B, C are the interior angles

So, 

A + B + C = 180°

C + A = 180° – B

Taking LHS 

tan (C + A)/2 = tan (180° – B)/2

= tan (90° – B)/2            -(∵ tan (90° – θ) = cot θ)

= cot B/2 = RHS 

LHS = RHS

Hence Proved

(ii) sin (B + C)/2 = cos A/2

Solution:  

According to the question

In triangle ABC, A, B, C are the interior angles

So, 

A + B + C = 180°

B + C = 180° – A

Taking LHS  

= sin (B + C)/2 = sin (180° – A)/2

= sin (90° – A/2)          -(∵ sin (90° – θ) = cos θ)

= cos A/2 

LHS = RHS

Hence Proved

Question 7. Prove that:

(i) tan20°tan35°tan45°tan55°tan70° = 1

Solution:

We have to prove that tan20°tan35°tan45°tan55°tan70° = 1

Taking LHS  

= tan20°tan35°tan45°tan55°tan70°

= tan(90° − 70°)tan(90° − 55°)tan45°tan55°tan70°          -(∵ tan (90° – θ) = cot θ)

= cot70°cot55°tan45°tan55°tan70°

= (1/tan70°)(1/tan55°)tan45°tan55°tan70°                 (∵ cot θ = 1/tan θ)

= tan45°

= 1 

LHS = RHS 

Hence Proved

(ii) sin48°sec42° + cos48°cosec42° = 2

Solution:

We have to prove that sin48°sec42° + cos48°cosec42° = 2

Taking LHS

= sin48°sec42° + cos48°cosec42°          (∵ sec θ = 1/cos θ and cosec θ = 1/sin θ)

\frac{sin48°}{cos(90°−48°)} + \frac{cos48°}{sin(90°−48°)}          -(∵ sin (90° – θ) = cos θ and cos (90° – θ) = sin θ)

= sin48°/sin48° + cos48°/cos48°

= 1 + 1

= 2

LHS = RHS

Hence Proved

(iii) \frac{sin 70°}{cos 20°}+\frac{cosec 20°}{sec 70°} – 2cos70° cosec20° = 0 

Solution:

We have to prove that \frac{sin 70°}{cos 20°}+\frac{cosec 20°}{sec 70°} – 2cos70° cosec20° = 0 

Taking LHS

= sin 70°/cos 20° + cosec 20°/sec 70° – 2cos70° cosec20°

\frac{sin 70°}{cos (90°-70°)} + \frac{cosec 20°}{sec(90°-20°)} - 2cos 70°cosec (90°-70°)

= sin 70°/sin 70° + cosec 20°/cosec 20° – 2cos 70°sec 70°

= 1 + 1 – 2cos 70°/cos 70°

= 0 

LHS = RHS 

Hence Proved



(iv) \frac{cos 80°}{sin 10°} + cos 59°cosec31° = 2

Solution:

We have to prove that \frac{cos 80°}{sin 10°} + cos 59°cosec31° = 2

Taking LHS 

= cos 80°/sin 10° + cos 59°cosec 31°

= cos 80°/sin (90° – 80°) + cos 59°cosec(90°-59°)

= cos 80°/cos 80° + cos 59°/cos 59°

= 1 + 1 = 2 

LHS = RHS 

Hence Proved




My Personal Notes arrow_drop_up
Recommended Articles
Page :